The effect of maternal body mass index on fetal growth: Use of individualized growth assessment and two‐level linear modeling. Issue 8 (2nd May 2014) - Canavan, Timothy P.; Deter, Russell L.
ABSTRACT Purpose To determine the effect of maternal body mass index on fetal growth using individualized growth assessment and two‐level linear modeling. Methods A retrospective review of biometry in the second and third trimesters from 246 normal, term singleton fetuses was performed. Four to eight biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), and femur diaphysis length (FDL) measurements per fetus were available and used to determine second‐trimester growth rates. Expected third‐trimester size trajectories were generated from these data and Percent Deviations [%Dev = ((observed − expected)/expected) × 100] were calculated. Two‐level linear modeling was used to determine %Dev slopes and the effect of body mass index (BMI) on these slopes. Relationships between individual second‐ and third‐trimester slopes and BMI were evaluated using linear regression. Results Linear regression analysis of second‐trimester growth indicated no significant relationships between the fetal growth rate and the BMI in the second trimester [R2 (adj): 0.0% to 1.0% except AC in one subgroup (5.6%)]. Regression analysis did not indicate a significant relationship (adj R2: 0%–0.2%) between BMI and third‐trimester %Dev slopes for any anatomic parameter. Two‐level statistical modeling showed no effect of BMI on BPD, AC, or FDL growth and only a moderate effect on the HC growth in the third trimester. Conclusions Our findings indicate that the maternal BMI does not have an effect on fetal growth in either the second or the third trimester as determined with individualized growth assessment. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:456–464, 2014